2011
DOI: 10.21460/jrmb.2011.61.73
|View full text |Cite
|
Sign up to set email alerts
|

Teknologi, Perdagangan Internasional Dan Pertumbuhan Ekonomi: Suatu Kajian Teori Ekonomi Klasik Ke Perdagangan Internasional Modern

Abstract: There are 3 phenomens of most economic which undivided that openess and international trade and economic growth. Openess is the first frame for most country to do consolidation for its capability and weakness. International trade have able support high economic growthsignificantly. This paper would like to inform us about development of international economic from Classical Economic era to Modern International Economic (integration of endogenous growth and trade). The analyzis is not only comparative static ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…A complete theory of economic growth must be able to describe what happens to the total gross domestic product and what happens to the population because if these two aspects are connected, it can also explain the development of output per capita. (Budiono, 2002). A country's economic growth does not always increase, but fluctuates due to various factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete theory of economic growth must be able to describe what happens to the total gross domestic product and what happens to the population because if these two aspects are connected, it can also explain the development of output per capita. (Budiono, 2002). A country's economic growth does not always increase, but fluctuates due to various factors.…”
Section: Introductionmentioning
confidence: 99%
“…Output per capita is total output divided by population, so the process of increasing output per capita must be analyzed by taking into account the total output on the one hand, and the population on the other. A complete theory of economic growth must be able to describe what happens to the total gross domestic product and what happens to the population because if these two aspects are connected, it can also explain the development of output per capita (Budiono, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This view is based on classical analysis, that the economy will continue to experiencefull employmentand capital equipment capacity will remain fully utilized over time (Budiono 2011) (Li and Huang 2021), with the title Dynamic relationship between economic policy uncertainty and growth Substantial economy in China The results show that the provisions on economic policies in China have a significant inhibitory effect on substantial economic growth. The results showed that the relationship between processes that have heterogeneous policies.…”
Section: Introductionmentioning
confidence: 99%
“…Hal itu berakibat naiknya pertumbuhan ekonomi negaranegara yang membuka perdagangan ekonominya. Naiknya pertumbuhan ekonomi juga akan meningkatkan kualitas kesejahteraan masyarakat (Budiono, 2011).…”
unclassified